B-103 Sexual transmission of HPV16 from Neandertals to modern humans and the evolution of viral oncogenesis. (March 2017) - Burk, Robert
Abstract : Human papillomavirus (HPV) type 16, a small circular double-stranded DNA virus, is the most oncogenic HPV and causes more than half of all cervix cancers. HPV16 is also the most common sexually transmitted viral infection. We have characterized and sequenced the complete genomes from HPV16 isolates throughout the world and will discuss viral variant lineages and phylogeny. Although analyses of HPV16 variants originally suggested codivergence with human population movement, recent discoveries on the origin of modern humans from multiple archaiclineages (e.g., Neandertals) suggests a more complex scenario. We have re-evaluated the origins of HPV16, using phylogeny-based approaches and estimated the timing of HPV16 diversion using Bayesian Markov Chain Monte Carlo (MCMC) methods. The divergence time of HPV16 A-lineage (Eurasian) and B/C/D-lineage (African) variants from their most recent common ancestor was estimated at approximately 500, 000 years ago, roughly coinciding with the split of modern humans and Neandertals. Moreover, we used principle coordinate analysis (PCoA) to examine the geographic clustering of over 3, 000 HPV16 variants. These analyses indicated that the A-lineage variants were significantly under-represented in Africa. Taken together, these data suggest that the currently circulating HPV16 A-lineage variants are the result of recent viral sexual transmission from Neanderthals to modern humans. These observations are consistent with multiple genetic introgressions of archaic hominins and modern humans through interbreeding in the past 80, 000 years and the massive recent expansion of Eurasian humans. The host genome was also found to influence the pathogenesis of HPV16 variant lineages. The evolution and pathogenesis of HPV16 provide insights into viral-host interactions.